Reading in English as a Foreign Language by Spanish Children With Dyslexia - Suárez-Coalla, Paz; Martínez-García, Cristina; Carnota, Andrés (Frontiers in Psychology, 2020)
It has been reported that children with dyslexia have difficulties learning a second language. The English alphabetic code is opaque, and it has been stated that deep orthographies cause important problems to children with dyslexia. Considering the strong differences between the Spanish and English orthographic systems, we predicted English reading problems in Spanish-speaking children with dyslexia. The current study focused on English as a foreign language in a group of twenty-two Spanish children with dyslexia (eight–twelve years old), compared to a control group matched for age, gender, grade, and socioeconomic status. The objective was to identify the main difficulties that Spanish-speaking children with dyslexia demonstrate during English reading, in order to develop specific teaching programmes. Participants were given four tasks related to reading: discrimination of phonemes, visual lexical decision, reading aloud, and oral vs. written semantic classification. The results suggest that children with dyslexia demonstrate problems in using English grapheme-phoneme rules, forcing them to employ a lexical strategy to read English words. However, they also showed difficulties in developing orthographic representations of words. Finally, they also exhibited problems with oral language, demonstrating difficulties accessing semantic information from an auditory presentation.